The Role of Microstructure and Surface Finish on the Corrosion of Selective Laser Melted 304L. Issue 5 (1st January 2018) - Schaller, Rebecca F.; Mishra, Ajit; Rodelas, Jeffrey M.; Taylor, Jason M.; Schindelholz, Eric J.
Abstract : The corrosion behavior of selective laser melted (SLM) 304L was investigated and compared to conventional wrought 304L in aqueous chloride and acidic solutions. Through immersed electrochemical testing and exposure in acidic solutions, the SLM 304L exhibited superior pitting resistance in the polished state compared to wrought 304L. However, the surface condition of the SLM material had a great impact on its corrosion resistance, with the grit-blasted condition exhibiting severely diminished pitting resistance. Local scale, capillary micro-electrochemical and scanning electrochemical microscopy investigations, identified porosity as a contributing factor to decreased corrosion resistance. Preferential corrosion attack was not observed to be related to the characteristic underlying cellular microstructure produced through SLM processing. This study highlights the effects of SLM microstructural features on corrosion resistance, specifically the substantial influence of surface finish on SLM corrosion behavior and the need for development and optimization of processing techniques to improve surface finish.